94.9k views
2 votes
-3x⁵+11x⁴+33x³-26x²-36x-6 / x³+6x²-3x-5​

-3x⁵+11x⁴+33x³-26x²-36x-6 / x³+6x²-3x-5​-example-1
User Dreamwagon
by
5.7k points

1 Answer

6 votes

Answer:


-3x^2+29x-150+(946x^2-341x-756)/(x^3+6x^2-3x-5)

Explanation:

You have to divide the polynomial
-3x^5+11x^4+33x^3-26x^2-36x-6 by the polynomial
x^3+6x^2-3x-5:

First, multiply the polynomial
x^3+6x^2-3x-5 by
-3x^2 and subtract the result from the polynomial
-3x^5+11x^4+33x^3-26x^2-36x-6:


-3x^5+11x^4+33x^3-26x^2-36x-6-(-3x^2)(x^3+6x^2-3x-5)\\ \\=-3x^5+11x^4+33x^3-26x^2-36x-6+3x^5+18x^4-9x^3-15x^2\\ \\=29x^4+24x^3-41x^2-36x-6

Now, multiply the polynomial
x^3+6x^2-3x-5 by
29x and subtract the result from the polynomial
29x^4+24x^3-41x^2-36x-6:


29x^4+24x^3-41x^2-36x-6-29x(x^3+6x^2-3x-5)\\ \\=29x^4+24x^3-41x^2-36x-6-29x^4-174x^3+87x^2+145x\\ \\=-150x^3+46x^2+109x-6

At last, multiply the polynomial
x^3+6x^2-3x-5 by
-150 and subtract the result from the polynomial
-150x^3+46x^2-181x-6:


-150x^3+46x^2+109x-6-(-150)(x^3+6x^2-3x-5)\\ \\=-150x^3+46x^2+109x-6+150x^3+900x^2-450x-750\\ \\=946x^2-341x-756

So,


(-3x^5+11x^4+33x^3-26x^2-36x-6)/(x^3+6x^2-3x-5)=\\ \\=((-3x^2+29x-150)(x^3+6x^2-3x-5)+946x^2-341x-756)/(x^3+6x^2-3x-5)=\\ \\=-3x^2+29x-150+(946x^2-341x-756)/(x^3+6x^2-3x-5)

User Disha
by
5.6k points